2009
DOI: 10.1007/s12098-009-0102-5
|View full text |Cite
|
Sign up to set email alerts
|

BFHI in a tertiary care hospital: Does being Baby friendly affect lactation success?

Abstract: To study the impact of Baby friendly policies on lactation success, a semi-structured questionnaire was administered to mothers of babies attending the well baby clinic of an urban tertiary care Baby Friendly Hospital. The feeding practices of outborn babies was compared to inborn babies (Baby friendly hospital). No major differences were found in the duration and success of lactation among the 2 groups. More intensive efforts and public awareness is required if the ideals of a baby friendly hospital are to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…A cross‐sectional Brazilian study that interviewed women with infants <5‐month‐old attending five community centres found that those delivering in BFHs (vs. non‐BFHs) had longer breastfeeding duration (Sampaio et al, ). A very low quality retrospective study conducted in India found no differences in prelacteal feedings or EBF among women who gave birth in a BFH vs. in non‐BFHs (Shilpa et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross‐sectional Brazilian study that interviewed women with infants <5‐month‐old attending five community centres found that those delivering in BFHs (vs. non‐BFHs) had longer breastfeeding duration (Sampaio et al, ). A very low quality retrospective study conducted in India found no differences in prelacteal feedings or EBF among women who gave birth in a BFH vs. in non‐BFHs (Shilpa et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Seven were conducted in Brazil, four in the United States and one each in Scotland, the UK, Russia, Puerto Rico, the Czech Republic, India, Nigeria, Switzerland and Taiwan. Eleven studies were classified as being of very low quality (Ojofeitimi et al, 2000;Weng et al, 2003;Bartington et al, 2006;Vieira et al, 2006;Rivera-Lugo et al, 2007;Rosenberg et al, 2008;Silva et al, 2008;Dabritz et al, 2009;Declercq et al, 2009;Narchi et al, 2009;Shilpa et al, 2009), six of low quality (Helsing et al, 2002;Venancio et al, 2002;Broadfoot et al, 2005;Merewood et al, 2005;Mydlilova et al, 2009;Sampaio et al, 2011) and three of moderate quality Merten et al, 2005;Venancio et al, 2012). Studies' description and findings.…”
Section: Cross-sectional/retrospectivementioning
confidence: 99%
“…[ 22 ] On the contrary, no major differences were found in duration and success of lactation among two groups in a study conducted at Baby-friendly Hospital at Bengaluru with a aim to find the impact of breastfeeding policies on lactation success. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%